1999
DOI: 10.1677/joe.0.160r007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the orexins on food intake: comparison with neuropeptide Y, melanin-concentrating hormone and galanin

Abstract: Orexin-A and orexin-B (the hypocretins) are recently described neuropeptides suggested to have a physiological role in the regulation of food intake in the rat. We compared the orexigenic effect of the orexins administered intracerebroventricular (ICV) with other known stimulants of food intake, one strong, neuropeptide Y (NPY), and two weaker, melanin-concentrating hormone (MCH) and galanin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
246
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(261 citation statements)
references
References 19 publications
9
246
0
3
Order By: Relevance
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
“…Through its hypothalamic effects, BDNF controls energy balance by enhancing catabolic processes (Xu et al, 2003). Similarly important are the actions of orexin neurons, situated in the LH and projecting to the NAc and VTA , to control food intake (Edwards et al, 1999;Harris et al, 2005) as well as drug reward and craving (Harris et al, 2005). In fact, a finding of a correlation between SGAs weight liability and the degree of LH orexin neurons stimulation ) is provocative and may offer important insights into homeostatic dysregulation associated with antipsychotic agents.…”
Section: Bdnfmentioning
confidence: 99%
“…Orexin (also known as hypocretin) is a neuropeptide that has been reported to play a role in the regulation of feeding, drinking, body temperature, general activity (Lubkin and Stricker-Krongrad, 1998;Edwards et al, 1999;Hagan et al, 1999;Kunii et al, 1999;Mondal et al, 1999;Piper et al, 2000;Estabrooke et al, 2001;Hungs et al, 2001;Yoshimichi et al, 2001;Kotz et al, 2002;Berthoud et al, 2005), energy homeostasis (Mintz et al, 2001), stimulation of gastric secretion in rats (Takahashi et al, 1999), increasing metabolic rate in rats (Lubkin and Stricker-Krongard, 1998), altering luteinising hormone release in rats (Pu et al, 1998) and in the regulation of the sleepwake cycle specifically associated with increased wakefulness and inhibition of REM sleep (Sakurai et al, 1998;Chemelli et al, 1999;Siegel, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Thannickal et al, 2000;van den Pol, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hypocretin/orexin, when injected intracerebroventricularly, increases food intake, energy expenditure, and locomotor activity [1,7,10]. Thus, hypocretin deficiency decreases appetite and energy expenditure, but the latter may have larger impact, resulting in a positive weight gain.…”
Section: Introductionmentioning
confidence: 99%